Поцелуй фортуны: [роман] / Елена Арсеньева - Арсеньева Елена Арсеньевна (Русская красавица, 2023)
Экземпляры: аб. ЦБ (20240520) / Инвентарный номер: 19171 / Цена: / Сис.шифр: 84(2=411.2)6 / Авт.знак: А 85 / ББК: 84(2=411.2)6-446